2017
DOI: 10.3389/fpsyg.2017.01863
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Empathy and Morality of Violent Video Game Characters on Gamers’ Aggression

Abstract: According to the General Aggression Model, situational factors (such as the game characters) and personal factors both affect a gamer’s acquisition of aggressive behavior. Previous studies have found not only that the surface features of game characters, such as appearance and clothing, but also that their inherent characteristics, such as morality and identity, can influence a gamer’s attitude and behavior. Research has also shown that empathy, as a personal factor, can protect gamers from the impact of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…For instance, a 3-year longitudinal study demonstrated that video-game violence did not increase aggression over time; rather, it was other factors, including levels of depression, exposure to family violence, antisocial personality traits, and peer influences, that emerged as influencing aggression levels (Ferguson, Miguel, Garza, & Jerabeck, 2012). Thus, it seems that family and social variables and the motivation behind the violence are more significantly related to an increase in aggression than the violence itself (Ferguson et al, 2015; Gao, Weng, Zhou, & Yu, 2017; Sauer, Drummond, & Nova, 2015). Indeed, even the gamer’s level of skill plays an important role in how these games affect aggression, such that the higher the levels of gaming skill, the lower the levels of aggression that are evident (Matthews, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a 3-year longitudinal study demonstrated that video-game violence did not increase aggression over time; rather, it was other factors, including levels of depression, exposure to family violence, antisocial personality traits, and peer influences, that emerged as influencing aggression levels (Ferguson, Miguel, Garza, & Jerabeck, 2012). Thus, it seems that family and social variables and the motivation behind the violence are more significantly related to an increase in aggression than the violence itself (Ferguson et al, 2015; Gao, Weng, Zhou, & Yu, 2017; Sauer, Drummond, & Nova, 2015). Indeed, even the gamer’s level of skill plays an important role in how these games affect aggression, such that the higher the levels of gaming skill, the lower the levels of aggression that are evident (Matthews, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Why do girls show increased aggressive cognition instead of aggressive behavior in a weapon toy condition? First, perhaps girls are better at restraining their aggressive cognition in order to inhibit aggressive behavior than boys in the context of weapon toys, whereas boys are more prone to take violent action in order to vent their anger than girls (Engelhardt et al, (Gao et al, 2017;Krahé & Möller, 2010). The nding indicates that parents and teachers should manage aggressive behavior for boys and girls in different ways when they are involved in weapon toy games.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby also accounting for differences between adolescent and adult game players in the level of VVGE to be measured as a continuous variable, and preferably measured objectively. Because the relationship might also work the other way around, it is plausible to assume that the individuals who less accurately recognized facial emotion expressions than the others may have a prior preference to play violent games (Sauer et al, 2015), or may self-report the games as more violent (Przybylski and Weinstein, 2021) and spend more time playing violent games (Gao et al, 2017). Therefore, future studies could measure to what extent the (lower) ability to recognize emotions, or empathy in general, may precede violent gameplay, preference of violent games, and VVGE overall.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%